A new subgenus of the stingless bee genus Melipona (Hymenoptera, Apidae), with a key to the subgenera - Melo, Gabriel A. R. (Acta Biológica Paranaense, 2021)
A new subgenus, Melipona (Meliponiella) (type-species: Melipona illustris Schwarz, 1932), is proposed to remedy the non-monophyly of M. (Eomelipona). A key to the subgenera of Melipona, based on the worker caste, is provided.